2008
DOI: 10.1017/s1355617708080594
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance image analysis of the cerebellum in macrocephalic and normocephalic children and adults with autism

Abstract: A detailed morphometric analysis of the cerebellum in autism with and without macrocephaly. Four subject groups (N 5 65; male; IQs Ն 65; age 7 to 26 years) were studied with quantitative MRI; normocephalic and macrocephalic individuals with autism without mental retardation were compared to normocephalic and benign macrocephalic typically developing individuals. Total cerebellum volumes and surface areas of four lobular midsagittal groups were measured. Independent t-tests between autism and control subjects m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 100 publications
2
8
0
Order By: Relevance
“…Postmortem neuroanatomical studies have consistently shown decreased Purkinjie cell density (Palmen 2004) in individuals with an ASD. Although morphological studies of the cerebellum have produced inconsistent results (Cleavinger et al 2008), diffusion tensor imaging (Catani et al 2008) and fMRI (Allen and Courchesne 2003) studies continue to support the presence of autism-related cerebellar abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem neuroanatomical studies have consistently shown decreased Purkinjie cell density (Palmen 2004) in individuals with an ASD. Although morphological studies of the cerebellum have produced inconsistent results (Cleavinger et al 2008), diffusion tensor imaging (Catani et al 2008) and fMRI (Allen and Courchesne 2003) studies continue to support the presence of autism-related cerebellar abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Each number represents a separate study: 1, Hashimoto et al, 1995; 2, Courchesne et al, 2001; 3, Akshoomoff et al, 2004; 4, Webb et al, 2009; 5, Carper et al, 2000; 6, Kleiman et al, 1992; 7, Kaufmann et al, 2003; 8, Kates et al, 2004; 9, Mitchell et. al., 2009; 10, Herbert et al, 2003; 11, Elia et al, 2000; 12, Cleavinger et. al., 2008; 13, Ciesielski et al, 1997; 14, Hardan et al, 2001; 15, Piven et al, 1992; 16, Hallahan et.…”
Section: Figurementioning
confidence: 99%
“…At the end of this process, 44 studies were selected, each assessing patients with idiopathic autism (i.e., DSM-IV diagnoses of either Autistic Disorder, Asperger's Disorder or Pervasive Developmental Disorder Not Otherwise Specified, PDD-NOS) and controls (Piven et al, 1995;Aylward et al, 1999;Haznedar et al, 2000;Hardan et al, 2000;Courchesne et al, 2001;Pierce and Couchesne, 2001;Aylward et al, 2002;Carper et al, 2002;McAlonan et al, 2002;Rojas et al, 2002;Sparks et al, 2002;Hardan et al, 2003;Herbert et al, 2003;Tsatsanis et al, 2003;Akshoomoff et al, 2004;Kates et al, 2004;Palmen et al, 2004;Schumann et al, 2004;Palmen et al, 2005;Vidal et al, 2006;Bloss and Courchesne, 2007;Girgis et al, 2007;Mostofsky et al, 2007;Tate et al, 2007;Cleavinger et al, 2008;Hardan et al, 2008;Freitag et al, 2009;Hallahan et al, 2009;Hardan et al, 2009;Scott et al, 2009;Bigler et al, 2010;Griebling et al, 2010;Jou et al, 2010aJou et al, , 2010bSchumann et al, 2010;Tamura et al, 2010;Tepest et al, 2010;Cheung et al, 2011;Hong et al, 2011;Calderoni et al, 2012;Greimel et al, 2012;…”
Section: 2study Selection Criteriamentioning
confidence: 99%